Diversification of Growth Media for Arabica Coffee Seedlings (Coffea arabica L) Through the Addition of Stalagmite Sediment and Guano Fertiliser from Goa Lawar Tangkahan, Langkat Regency - Bima Kirana Sembiring; Andi Setiawan; Kabul Warsito (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
highlights the need for innovation in nursery media based on locally available organic materials. This study aimed to analyze the effects of guano fertilizer and stalagmite sediment originating from Lawar Cave, Tangkahan, Langkat Regency, on the early growth of Arabica coffee seedlings (Coffea arabica L.). The research was conducted in Kutalimbaru District, Deli Serdang Regency, from May to July 2025 using a factorial Randomized Block Design (RBD) with two factors: guano fertilizer (0, 50, 100, and 150 g/polybag) and stalagmite sediment (0, 20, 30, and 40 g/polybag), with three replications. The observed parameters included plant height, number of leaves, leaf area, and root length. Data were analyzed using analysis of variance (ANOVA) followed by Duncan’s Multiple Range Test at the 5% significance level. The results showed that the interaction between guano fertilizer and stalagmite sediment had significant to highly significant effects on plant height and number of leaves. Application of guano at 50 g/polybag increased plant height by 1.38%, while stalagmite sediment at 30 g/polybag increased plant height by up to 2.97%. The highest number of leaves was obtained with guano at 150 g/polybag, showing an increase of 5.15%. Root length was significantly affected by stalagmite sediment, with an increase of up to 6.03%, whereas leaf area showed no significant differences among treatments. It can be concluded that the combination of guano fertilizer and stalagmite sediment effectively enhances the early growth of Arabica coffee seedlings and has strong potential to support sustainable coffee nursery systems.Research purposes.